2011
DOI: 10.1002/art.30613
|View full text |Cite
|
Sign up to set email alerts
|

A phase III, randomized, placebo-controlled study of belimumab, a monoclonal antibody that inhibits B lymphocyte stimulator, in patients with systemic lupus erythematosus

Abstract: Objective To assess the efficacy/safety of the B-lymphocyte stimulator inhibitor belimumab/standard-of-care (SOC) versus placebo/SOC in active systemic lupus erythematosus (SLE). Methods In a multicenter, randomized, controlled, phase 3 trial, 819 antinuclear antibody- or anti-dsDNA-positive SLE patients with Safety of Estrogens in Lupus Erythematosus National Assessment–SLE Disease Activity Index (SELENA-SLEDAI) ≥ 6 were randomized (1:1:1 ratio) to receive intravenous belimumab 1 or 10 mg/kg, or placebo on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

62
1,250
4
53

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,415 publications
(1,419 citation statements)
references
References 29 publications
62
1,250
4
53
Order By: Relevance
“…Safety data were consistent with the known safety profile of belimumab,3, 4 and the majority of subjects (94%) had successful self‐injections, indicating a high level of usability and reliability for the devices.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Safety data were consistent with the known safety profile of belimumab,3, 4 and the majority of subjects (94%) had successful self‐injections, indicating a high level of usability and reliability for the devices.…”
Section: Discussionsupporting
confidence: 70%
“…Belimumab is a recombinant human immunoglobulin (Ig) G1λ monoclonal antibody that binds and antagonizes the biological activity of soluble B‐lymphocyte stimulator (BLyS), a member of the tumor necrosis factor ligand superfamily, which promotes the survival of B lymphocytes 2. Following completion of 2 large, multicenter, randomized, controlled trials, belimumab was approved for the treatment of adults with active, autoantibody‐positive SLE in combination with standard therapy 3, 4…”
mentioning
confidence: 99%
“…In the BLISS‐52 and BLISS‐76 studies, rates of severe SFI flare were 14% (40 of 290 patients) and 21% (56 of 273 patients), respectively 13, 14, among patients who received 10 mg/kg belimumab. In this continuation study, the percentage of patients experiencing a new severe SFI flare between the study year 1 and study year 7 midpoints was low; the cumulative count increased from 15 of 267 patients (5.6%) to 55 of 267 patients (20.6%) during this period.…”
Section: Discussionmentioning
confidence: 99%
“…A placebo‐controlled phase II study showed that intravenous (IV) belimumab plus standard therapy was generally well tolerated 11; a good safety profile was maintained over 7 years 12. Two phase III studies, the Study of Belimumab in Subjects with SLE 52‐week (BLISS‐52) and 76‐week (BLISS‐76) trials, demonstrated the safety and efficacy of belimumab in patients with autoantibody‐positive, active SLE 13, 14. The long‐term safety and efficacy of belimumab were examined in 2 open‐label continuation studies (GlaxoSmithKline [GSK] studies BEL112233 and BEL112234) in patients who completed the BLISS studies.…”
mentioning
confidence: 99%
“…The BILAG‐2004 category scores A to E are based on intention to treat, where A = severe disease activity, B = moderate disease activity, C = mild, stable disease, D = inactive disease but previously affected system, and E = a system that has never been involved. Changes in overall disease activity between consecutive time points, as measured by the BILAG‐2004 index, were defined as follows: 1) deterioration, with any system changing to A from B/C/D or to B from C/D 21; 2) improvement, with all systems changing from A to B/C/D and B scores changing to C/D 22, with no deterioration in any system (one persistent B score was allowed if there was improvement from A or B in at least 1 other system); 3) persistent inactive disease, with all systems scored as C/D/E at both time points; and 4) persistent active disease, with A or B system scores remaining unchanged but without overall improvement or deterioration. When changes of activity of a single BILAG system were analyzed, the above definitions applied, but only for that system, and no persistent B score was allowable for improvement.…”
Section: Methodsmentioning
confidence: 99%